Aplikasi Pendidikan Dakwah Menggunakan Media Komunikasi Visual Komik Religi - Chotib, Sjahidul Haq (MADINAH, 2017)
Da’wah activity today is not enough by using traditional media, such as through lectures and studies that still use oral communication media or speech. The use of modern communication media in accordance with the level of the development of human fikir power should be utilized in such a way, so that the da'wah of Islam is more targeted and not out of date, the da'wah is the actualization of faith (theologically) manifested in a system of human activity of belief systematically, to give suggestions of ways of thinking and acting within the framework of individual and social according to Islamic teachings. Examples are the application of online media communication technology, social networking, radio, visual, cinematography and others. This discussion only leads to visual communication in the use of Islamic comic medium.